TINDAK PIDANA DALAM JUAL BELI SEPEDA MOTOR YANG DIBIAYAI OLEH LEMBAGA PEMBIAYAAN (PROBLEMATIK PELAKSANAAN DI LAPANGAN) - Hartanto Hartanto (Institut Agama Islam Negeri (IAIN) Kendari, 2019)
Motorcycle is a means of transportation that is quite efficient and effective in supporting community activities. Motorcycle like other products that are sold not only by cash system (cash), but most of it is actually credit (buying and selling with credit / installments). This raises the problem of the occurrence of criminal acts of buying and selling motorbikes financed by financial institutions and its completion. Problems in the field show there are bad ideas from consumers and there are bad ties from employees of financial institutions due to the emergence of the use of